A generational catastrophe: COVID-19 and children's access to education and food in South Africa. Issue 5 (3rd September 2022) - Shepherd, Debra; Mohohlwane, Nompumelelo
ABSTRACT: Since the onset of the COVID-19 pandemic, children have been put at greater risk of school drop-out, as well as food insecurity and emotional health deterioration. This paper considers these issues as they have occurred in South Africa. We use all waves of the National Income Dynamics Study–Coronavirus Rapid Mobile Survey to estimate non-return to school, access to school meals, and household well-being. The number of learners not attending school in 2021 is estimated to be close to quadruple pre-pandemic levels. Combined with estimates of learning lost, we can conclude that the pandemic has worn away at two decades of progress made in basic education. Evidence also indicates that school feeding has been slow to recover to pre-pandemic levels. Deepened levels of household hunger combined with a lack of access to free school meals is indicated to contribute to significantly greater levels of caregiver anxiety and psychological distress.